2006
DOI: 10.1101/gad.386706
|View full text |Cite
|
Sign up to set email alerts
|

A role for the catalytic ribonucleoprotein RNase P in RNA polymerase III transcription

Abstract: Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 52 publications
4
131
0
1
Order By: Relevance
“…It is known that Rpp20 and Rpp25 have chromatin-binding capabilities. 40,41) Furthermore, the heterodimerization of Rpp20 and Rpp25 regulates their RNA-binding activity, subcellular localization, and expression. 19) A recent study showed that human nuclear RNase P is required for transcription of tRNA and other small noncoding RNA genes by pol III, and Rpp20 and Rpp25 are expected to play an essential role in this function as chromatin-binding proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that Rpp20 and Rpp25 have chromatin-binding capabilities. 40,41) Furthermore, the heterodimerization of Rpp20 and Rpp25 regulates their RNA-binding activity, subcellular localization, and expression. 19) A recent study showed that human nuclear RNase P is required for transcription of tRNA and other small noncoding RNA genes by pol III, and Rpp20 and Rpp25 are expected to play an essential role in this function as chromatin-binding proteins.…”
Section: Resultsmentioning
confidence: 99%
“…RNase P activity was shown (Reiner et al 2006) to coimmunoprecipitate with components of Pol III; depletion of RNase P resulted in significant reduction of the level of transcription of tRNA Tyr , tRNA Met , 5S rRNA, 7SL RNA, and U6 snRNA in HeLa cell extracts, and this effect was reversed by the addition of RNase P. Moreover, the knockdown of protein components of RNase P practically abolished Pol III transcription of 5S rRNA in whole HeLa cells. In addition, chromatin immunoprecipitation indicated that all analyzed protein components of RNase P associated with chromatin of actively transcribed, but not inactive, tRNA and 5S rRNA genes (Reiner et al 2006;Jarrous and Reiner 2007). A very similar effect of the presence of RNase P was recently reported for rRNA transcription by RNA polymerase I (Reiner et al 2008).…”
Section: Eukaryotic Rnase P In Transcriptionmentioning
confidence: 96%
“…RNase MRP is closely related to RNase P, but it has evolved to have a different specificity. RNase P is responsible for the 59-end maturation of tRNA and is involved in processing of other RNAs, including rRNA (Kazantsev and Pace 2006;Kirsebom 2007); RNase P was also shown to have a role in transcription (Reiner et al 2006). The vast majority of RNase MRP is located in the nucleolus (Kiss and Filipowicz 1992).…”
Section: Introductionmentioning
confidence: 99%